Γ-Synuclein Induces Human Cortical Astrocyte Proliferation and Subsequent BDNF Expression and Release. (1st July 2019) - Winham, Cynthia L.; Le, Timmy; Jellison, Evan R.; Silver, Adam C.; Levesque, Aime A.; Koob, Andrew O.
Abstract: γ-Synuclein (γ-syn) is expressed by astrocytes in the human nervous system, and increased extracellularly in the brain and cerebrospinal fluid of individuals diagnosed with Alzheimer's disease. Upregulation of γ-syn also coincides with proliferation of glioblastomas and other cancers. In order to better understand regulation and function of extracellular γ-syn, primary human cortical astrocytes were treated with γ-syn conditioned media at various physiological concentrations (50, 100, 150 nM) after cell synchronization. Additionally, extracellular brain-derived neurotrophic factor (BDNF), a neuroprotective growth factor released by astrocytes that has been shown to be decreased extracellularly in neurodegenerative disease, was observed in response to γ-syn treatment. Analysis of 5-bromodeoxyuridine (BrdU) and propidium iodide through flow cytometry 24 h after release from synchronization revealed an increase in G2 /M phase of the cell cycle with 100 nM γ-syn during initial cell division, an effect that was reversed at 48 h. However, increased extracellular BDNF was observed at 48 h with 100 nM and 150 nM γ-syn treatment with no difference between controls at 24 h. Further analysis of cell cycle markers with immunocytochemistry of BrdU and Ki67 after treatment with 100 nM γ-syn confirmed increased initial cell proliferation and decreased non-proliferating cells. Western blot analysis demonstrated increased γ-syn levels after 100 nM treatment at 24 and 48 h, and increased pro-BDNF, mature BDNF and cell viability at 48 h. The results demonstrate that γ-syn internalization by human cortical astrocytes causes upregulation of the cell cycle, followed by subsequent BDNF expression and release. Highlights: Primary human cortical astrocyte proliferation increases in response to γ-synuclein treatment Extracellular γ-synuclein is internalized by human cortical astrocytes Increased astrocyte proliferation in response to γ-synuclein is followed by elevated BDNF expression and release Increased BDNF expression induced by γ-synuclein also coincides with improved cell viability